Eastern Europe in 1968 Responses to the Prague Spring and Warsaw Pact Invasion (Springer International Publishing, 2018)
This collection of thirteen essays examines reactions in Eastern Europe to the Prague Spring and Warsaw Pact invasion of Czechoslovakia in 1968. Countries covered include the Soviet Union and specific Soviet republics (Ukraine, Moldavia, the Baltic States), together with two chapters on Czechoslovakia and one each on East Germany, Poland, Hungary, Bulgaria, Romania, Yugoslavia and Albania. The individual contributions explain why most of these communist regimes opposed Alexander Dubček's reforms and supported the Soviet-led military intervention in August 1968, and why some stood apart. They also explore public reactions in Eastern Europe to the events of 1968, including instances of popular opposition to the crushing of the Prague Spring, expressions of loyalty to Soviet-style socialism, and cases of indifference or uncertainty. Among the many complex legacies of the East European '1968' was the development of new ways of thinking about regional identity, state borders, de-Stalinisation and the burdens of the past. .